언어 네트워크 분석을 통한 노인 구강 건강 연구 동향 탐구 - 김윤정; Yun-jeong Kim (Han'guk Ch'iwisaeng Hakhoe chi, 2023)
Objectives: The purpose of this study is to explore the research trends of elderly oral health through a language network analysis. Methods: A total of 354 published studies with 668 keywords were collected from the Research Information Sharing Service (RISS) between 2000 and 2022. Language network analysis was performed using Textom 6.0, Ucinet 6.774, and NetDraw 2.183. Results: The most frequent keywords were ‘elderly’, ‘oral health’, ‘quality of life’, and ‘OHIP-14’. The result of frequency-inverse document frequent keywords showed similar results to the most frequent keywords. The N-gram of keywords shows that ‘elderly’, ‘oral health’ (18 times) and ‘elderly’, ‘depression’ (7 times). As a results of the analysis of degree centrality and between centrality, ‘elderly’, ‘oral health’, and ‘quality of life’ were found to be high. The CONCOR analysis identified the main clusters of ‘quality of life’, ‘oral health behavior’, ‘health’, and ‘oral function disorder’. Conclusions: The results of the current study could be available to know research trends in elderly oral health and it is necessary to improve more comprehensive study in follow-up study.